Sistem Pemerintahan Kedatuan Luwu dalam Kurung Periode I Lagaligo (Abad IX-XIII) - Syamzan Syukur (Rihlah : Jurnal Sejarah dan Kebudayaan, 2015)
Luwu was the oldest kingdom in South Celebes. Luwu had been known as the origin place of Buginese civilization which appeared since 10th century. Therefore, it is so interesting to know more about Luwu. Then, the concern of this research is to explore the goverment system of Luwu in the era of La Galigo in 9-13th centuries. It should be understood that La Galigo is a classic manuscript which describe about the origin people of Luwu. In this case Luwu represents the oldest Buginese ethnic. Further, in La Galigo we will find a story (or even a myth) about the famous person, named Sawerigading. He and his family i.e. Batara Guru as his father and La Galigo as his son had created a new social-political stratum in the Buginese society. Sawerigading played a role as a charismatic person which in this case he became as symbol of his ethnic. According to that condition, we can analyze that the earliest government system of Luwu Kingdom is monarchi absolute. Thus that goverment system appropriates with the social condition of society which had a belief to gods or it calls urmonotheism i.e. PatotoE (as the highest God of Buginese/Luwu society).